ANALISIS HUBUNGAN KEMAMPUAN BERPIKIR FORMAL DENGAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN KIMIA DI KELAS X SMA NEGERI 9 PONTIANAK - Juliansyah Juliansyah; Tuti Kurniati; Fitriani Fitriani (Universitas Muhammadiyah Pontianak, 2016)
ABSTRACTThe complex and abstract characteristics of Chemical materials requires students to have higher thinking skills to learn. Relationship of students' thinking skills and the ability to learn chemistry indicates the need of formal thinking skills in learning chemistry. This study aimed at describing the grade X students’ thinking skills and learning outcomes, and finding the correlation of grade X students’ learning outcomes and their formal thinking skills. The results of analysis revealed that as many as 7 students were able to correctly answer the burney test questions and achieved value range of 17-24. This value was included in the criteria of formal thinking. In addition, the preferred correct answers were the correlation a land combinatorial reasoning. A total of 10 students of grade XD, SMA Negeri 9 Pontianak obtained test results of chemistry achievement at ≥ 65, while 26 students scored completeness at ≤ 65. The data obtained showed the positive correlation between formal thinking skills and learning outcomes with correlation coefficient sof 0.514 or 51.4%. Hence, it can be concluded that there is a positive relationship of formal thinking skills and students’ learning outcomes in learning chemistry.Keywords : Students’ learning outcomes, The ability of Formal thinking, Learning Chemistry